Implementasi Corporate Sosial Responsibility PT Riau Crumb Rubber Factory terhadap Masyarakat Kelurahan Sri Meranti Kota Pekanbaru - Andrew Shandy Utama; Rizana Rizana (Universitas Ahmad Dahlan, 2017)
A company that carries out its business activities in the field and/or related to natural resources is obliged to carry out its Corporate Social Responsibility (CSR). This research was conducted at PT Riau Crumb Rubber Factory which is located in Sri Meranti Village. Raw rubber production activities into semi-finished rubbers have been routinely generating pollution for the environment and society, such as air pollution and water pollution. The problem is how the implementation of CSR PT Riau Crumb Rubber Factory to the community of Sri Meranti Village in Pekanbaru City? What are the obstacles and the legal effort based on Riau Province Regional Regulation Number 6 Year 2012? This research is a sociological law research. Source of data used in this research is primary data and secondary data. Data collection techniques used in this study are observation, interview, and literature study. Data analysis technique used in this research is qualitative analysis. The result of this research is PT Riau Crumb Rubber Factory has implemented CSR, but has not fulfilled the expectation the community of Sri Meranti Village because it is not comparable with the pollution and environmental damage caused by the company's operational activities. The obstacle from the company side is the limited budget of CSR funds owned by PT Riau Crumb Rubber Factory to be able to meet all the needs of the community, while from the community side is the lack of legal knowledge of the community of Sri Meranti Village about CSR. The legal effort is that if PT Riau Crumb Rubber Factory does not implement CSR, the community of Sri Meranti Village can convey their aspirations to the DPRD of Riau Province for the company to be recommended to get administrative sanction from the government, such as the suspension of operational license of the company.